Prevalence and Mechanisms of Partial Migration in Ungulates - Berg, Jodi E.; Hebblewhite, Mark; St. Clair, Colleen C.; Merrill, Evelyn H. (Frontiers in Ecology and Evolution, 2019)
Partial migration, a phenomenon wherein only some individuals within a population migrate, is taxonomically widespread. While well-studied in birds and fish, partial migration in large herbivores has come into the spotlight only recently due to the decline of migratory behavior in ungulate species around the world. We reviewed studies describing these trends to explore both population- and individual-level mechanisms for partial migration in ungulates. We addressed how density-dependent and -independent factors, alone or together, could maintain both migrants and residents within a population. We then searched for evidence that intrinsic and extrinsic factors could combine with genetic predispositions and individual differences in temperament or life experience to promote migratory tendencies of individuals. Despite the long-held assumption that migration is a fixed behavior of individuals, evidence suggested that changes in migratory behavior result from state-dependent responses of individuals. Data are needed to demonstrate empirically which factors determine the relative costs and benefits to using migratory versus resident tactics. We outline what types of long-term data could address this need and urge those studying migration to meet these challenges in the interest of conserving partially migratory populations.